1960
DOI: 10.1577/1548-8659(1960)89[263:tscari]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Stoneroller, Campostoma anomalum (Rafinesque), in Great Smoky Mountains National Park

Abstract: The stoneroller (Campostoma anomalum) is one of the more important fish in Great Smoky Mountains National Park because of its abundance and habits. Although esteemed locally as a food and a bait fish, the stoneroller is exploited but little since the fishing regulations which govern the utilization of game fishes afford it a large measure of protection. Distribution is controlled by gradient with an upper limit of 4.4 percent. Stonerollers limit reproduction of rainbow trout (Salmo gairdneri) by destroying tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This study presents the first quantitative description of central stoneroller spawning microhabitat preference, although some qualitative descriptions of habitat and behaviors have been presented such as communal broadcast spawning in pool tails (Smith 1935;Lennon & Parker 1960;Miller 1962;Miller 1964;Jenkins & Burkhead 1994). Microhabitat variables measured in this study match the general qualitative descriptions provided by Miller (1962) and Lennon & Parker (1960). Central stoneroller is widespread throughout the eastern United States and Canada, and at least six distinct evolutionary entities of this polytypic species are recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study presents the first quantitative description of central stoneroller spawning microhabitat preference, although some qualitative descriptions of habitat and behaviors have been presented such as communal broadcast spawning in pool tails (Smith 1935;Lennon & Parker 1960;Miller 1962;Miller 1964;Jenkins & Burkhead 1994). Microhabitat variables measured in this study match the general qualitative descriptions provided by Miller (1962) and Lennon & Parker (1960). Central stoneroller is widespread throughout the eastern United States and Canada, and at least six distinct evolutionary entities of this polytypic species are recognized.…”
Section: Discussionmentioning
confidence: 99%
“…In general, stonerollers spawn in mid-spring in pit-like nests dug out by large males. Some stonerollers may also spawn on unmodified substrate in riffles (Miller 1962), on gravel mound nests constructed by male Nocomis chubs (Reighard 1943), or even on redds of rainbow trout Oncorhynchus mykiss (Lennon & Parker 1960). Although stoneroller spawning behavior is well observed, no studies have quantified preference for nesting microhabitat variables such as substrate size, depth, and current velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators (Smith 193.5, Trautman 1981) have reported that C. anomalum make substantial seasonal migrations in some streams, whereas fish in other systems exhibit only small (if any), localized movements (Lennon & Parker 1960, Miller 1962. In this paper we present data on movements and densities of C. anomalum in a small Ohio stream during autumn, and estimate its home range.…”
Section: Introductionmentioning
confidence: 88%
“…Berra & Gunning 1972). It remains questionable whether or not C. anomalum makes a spawning migration (Lennon & Parker 1960, Miller 1962, Trautman 1981. More examination is needed to determine if the species exhibits a true spawning migration, and if so, whether the fish return to their original home ranges following spawning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation